Oxidative stress in disease: cardiac ischemia/reperfusion injury - Zweier, Jay (Henry Stewart Talks, 2007)
Reperfusion injury, Oxygen radicals are mediators of injury, Reperfusion radical generation and duration of ischemia, SOD1 and reperfusion, Xanthine oxidase as a source of radical generation, Xanthine oxidase substrates are formed during ischemia, Superoxide and adhesion molecule expression, Post-ischemic injury and leukocytes, NO generation during ischemia, NO-heme complexes in ischemic heart, Maximizing myocardial salvage, EPR imaging
Archived at 2018/05/31